Quality Assurance: A Mechanism for Effective Management of Secondary School for Improvement - Tijani, Abdulganiyu Adebayo; Abdullahi, Nimota Jibola Kadir (International Journal of Educational Management, 2022)
This paper examined the Quality Assurance as a mechanism for Secondary School improvement in Kwara State. Some of the vital issues discussed in the paper are: the concept of quality assurance, problems of quality assurance, and quality assurance as a mechanism for improving secondary school administration. The paper concluded that quality assurance mechanism, if properly utilized could be a proper means of improving secondary school system and which will further enhance Student Academic Performance. The paper thus suggested that Government through the State Ministry of Education should energized its quality assurance unit through proper funding and necessary logistics required for monitoring of secondary schools. The principals of school should not limit their administration to offices but rather thorough supervision of instruction as internal quality assurance manager for school management and improvement.